Organic acid-mediated phosphorus mobilization in black soils: differential effects of maize root exudates on alfisols and mollisols in Northeast China - Wenzhi Zhao; Yuan Zhang; Xu Xie; He Li; Jintao Zhang (PLoS ONE, 2025)
Soil phosphorus exists in various forms, but only minimal soluble phosphorus is bioavailable. While phosphate fertilizers address deficiency, low efficiency leads to insoluble phosphate accumulation, wasting resources. Enhancing phosphorus availability by converting non-available forms is a critical research priority. Under phosphorus-deficient conditions, plants enhance soil phosphorus availability by secreting organic acids. This study aims to explore phosphorus activation in Alfisol and Mollisol soils through maize root-secreted organic acids. Semi-hydroponic maize cultivation under low/medium/high phosphorus levels and sterilized soil (Alfisol/Mollisol) incubation with root-secreted organic acids (0.5–2%). Exudates analyzed via UHPLC-MS/MS; soil phosphorus dynamics monitored over 60 days. Under phosphorus limitation, maize root exudates showed marked increases in malic, citric, tartaric, and trans-aconitic acids. Soil incubation revealed peak phosphorus release during 0–20 d, with Alfisol exhibiting 95.8% (tartaric), 91.1% (citric), 81.8% (malic), and 67.7% (trans-aconitic) increases in available phosphorus, while Mollisol showed 94.0%, 119.6%, 83.1%, and 75.2% increments, respectively. Tartaric and citric acids outperformed others, boosting H2O-P and NaHCO3-Pi, whereas malic and trans-aconitic acids mainly elevated NaHCO3-Pi. Fractionation analysis highlighted distinct mechanisms: citric acid primarily mobilizes HCl-P; malic acid mainly targets NaOH-Pi and HCl-P; tartaric acid mobilizes NaOH-Po, HCl-P, and NaOH-Pi; while trans-aconitic acid influences NaOH-Po, HCl-P, and Res-P. These findings demonstrate acid-specific phosphorus pool mobilization, identifying tartaric and citric acids as most effective, supporting optimized phosphorus management strategies in black soils.